The protective effects of naproxen against interleukin-1β (IL-1β)- induced damage in human umbilical vein endothelial cells (HUVECs). Issue 1 (1st January 2021) - Wu, Yuliang; Hao, Ruina; Lan, Beidi; Mu, Yiping; Dang, Fuping; Wang, Ruitao
ABSTRACT: Non-steroidal anti-inflammatory drugs (NSAIDs) are one of the most widely used medications in the world. Naproxen is an NSAID with relatively low selectivity for cyclooxygenase-2 (COX-2), thereby having decreased risk for cardiovascular (CV) events. However, it is unclear whether naproxen might provide protection against atherosclerosis, an underlying cause of numerous cardiovascular diseases (CVDs). In the present study, we exposed human umbilical vein endothelial cells to interleukin-1β (IL-1β), a key cytokine involved in atherogenesis, with or without naproxen. Our findings indicate that naproxen could protect against IL-1β-induced damage by improving cell viability and preventing cell death. Additionally, naproxen suppressed the expression of the cytokines IL-6, IL-12, and tumor necrosis factor-α (TNF-α), and downregulated the expression of vascular endothelial growth factor (VEGF) and tissue factor (TF) induced by IL-1β. Importantly, naproxen also inhibited the attachment of monocytes to endothelial cells, which was achieved through Krüppel-like factor 6 (KLF6)-mediated reduced expression of intracellular adhesion molecule-1 (ICAM-1) and E-selectin. These findings suggest that naproxen may aid in the prevention of atherosclerosis by exerting cardioprotective effects beyond low COX-2-selectivity. Graphical Abstract: uf0001